Travel-related health events and their risk factors in HIV-infected sub-Saharan migrants living in France and visiting their native country: The ANRS VIHVO cohort study. Issue 29 (May 2019) - ; Bentata, Michele; Fantin, Bruno; Goujard, Cécile; Matheron, Sophie; Launay, Odile; Le Moing, Vincent; Lortholary, Olivier; Consigny, Paul- Henri; Saada, Matthieu; Katlama, Christine; Simon, Anne; et al.
Abstract: Background: Literature on health events in HIV-infected travellers is scarce, particularly in sub-Saharan African (SSA) migrants. Methods: We investigated health events in HIV-infected SSA migrants living in France during and after travel to their native country. All had a pre-travel plasma viral load (pVL) below 200 copies/mL and were on stable combined antiretroviral therapy (cART). Logistic regression models were used to assess the risk factors for at least one adverse health event or febrile event. Results: Among 264 HIV migrants, pre-travel median CD4 count was 439/mm3 and 27 migrants (6%) experienced a low-level viremia between 50 and 200 copies/mL. One hundred (38%) experienced at least one event (13 experienced two events). The most common events were gastrointestinal, including diarrhoea (n = 29, 26%), respiratory events (n = 20, 18%), and malaria (n = 17, 15%; 1 death). In multivariable analysis, a pre-travel low-level viremia and a lack of pre-travel medical advice significantly increased the risk for any event (OR 4.31, 95% CI, 1.41–13.1; and OR 3.62, 95% CI, 1.38–9.47; respectively). A lack of pre-travel advice significantly increased the risk for febrile event. Conclusions: Early and tailored counselling on pre-travel medical advice regarding diarrhoea and vector-borne diseases prophylactic measures in HIV-infected SSA migrants should be emphasised before travel to Africa.